Mummies and masquerades: English and Caribbean connections - Millington, Peter; James, Caspar (2013)
The composite mumming play script that the Ecclesfield-based Victorian children's author Juliana Horatia Ewing published in 1884 found its way to St. Kitts and Nevis in the Caribbean, where it was it was taken up enthusiastically by the black population as one of its Christmas Sports. The Mummies continue to act (and dance) to this day. Economic migrants took the Christmas Sports in turn to the Dominican Republic, in particular around the town of San Pedro de Macoris, where the performers recently gained a UNESCO Cultural Heritage Award. This paper derives from a presentation based around two videos, presented here as story boards. Millington introduces Ewing's play, and footage of the St Kitts Mummies and the Bull Play filmed by Joan McMurray. James continues the story by introducing footage of the related tradition from the Dominican Republic called the Wild Indians in English and Los Guloyas (the Goliaths) in Spanish.